Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae) - Zhang, Bin; Wang, Chin-Fah (Zootaxa, 2018)
A new genus of poplar-feeding leafhopper, Henanocerus gen. nov., comprising a single species (Henanocerus lineatus sp. nov.) is described and illustrated. This new genus is placed only tentatively in the tribe Idiocerini of subfamily Idiocerinae based on the structure of the external morphology.